The Deubiquitinating Enzyme Inhibitor PR-619 Enhances the Cytotoxicity of Cisplatin via the Suppression of Anti-Apoptotic Bcl-2 Protein: In Vitro and In Vivo Study - Kuan-Lin Kuo; Shing-Hwa Liu; Wei-Chou Lin; Po-Ming Chow; Yu-Wei Chang; Shao-Ping Yang; Chung-Sheng Shi; Chen-Hsun Hsu; Shih-Ming Liao; Hong-Chiang Chang; Kuo-How Huang (Cells, 2019)
After chemotherapy for the treatment of metastatic bladder urothelial carcinoma (UC), most patients inevitably encounter drug resistance and resultant treatment failure. Deubiquitinating enzymes (DUBs) remove ubiquitin from target proteins and play a critical role in maintaining protein homeostasis. This study investigated the antitumor effect of PR-619, a DUBs inhibitor, in combination with cisplatin, for bladder UC treatment. Our results showed that PR-619 effectively induced dose- and time-dependent cytotoxicity, apoptosis, and ER-stress related apoptosis in human UC (T24 and BFTC-905) cells. Additionally, co-treatment of PR-619 with cisplatin potentiated cisplatin-induced cytotoxicity in UC cells and was accompanied by the concurrent suppression of Bcl-2. We also proved that Bcl-2 overexpression is related to the chemo-resistant status in patients with metastatic UC by immunohistochemistry (IHC) staining. In a xenograft mice model, we confirmed that PR-619 enhanced the antitumor effect of cisplatin on cisplatin-naïve and cisplatin-resistant UCs. Our results demonstrated that PR-619 effectively enhanced the cisplatin-induced antitumor effect via concurrent suppression of the Bcl-2 level. These findings provide promising insight for developing a therapeutic strategy for UC treatment.